Peranan Kawasan Industri dalam Mengatasi Gejala Deindustrialisasi - Winardi, Winardi; Priyarsono, D. S.; Siregar, Hermanto; Kustanto, Heru (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
Industrial area is one of the determinant factors in the development of manufacturing industry in a region. Theoretically, industrial companies located in industrial areas have an impact on increasing productivity, added value, efficiency, and economic income of a region. This research aims to analyze the role of industrial area in overcoming the deindustrialization symptom with Social Accounting Matrix Model. The result of analysis shows that industrial area has an important role in increasing the output of economy and the absorption of bigger workforce so that indirectly will have an impact on acceleration of industrialization process and also to overcome deindustrialization.